2017
DOI: 10.3389/fnagi.2017.00189
|View full text |Cite|
|
Sign up to set email alerts
|

Oscillatory Activities in Neurological Disorders of Elderly: Biomarkers to Target for Neuromodulation

Abstract: Non-invasive brain stimulation (NIBS) has been under investigation as adjunct treatment of various neurological disorders with variable success. One challenge is the limited knowledge on what would be effective neuronal targets for an intervention, combined with limited knowledge on the neuronal mechanisms of NIBS. Motivated on the one hand by recent evidence that oscillatory activities in neural systems play a role in orchestrating brain functions and dysfunctions, in particular those of neurological disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 217 publications
1
52
3
Order By: Relevance
“…Delta waves (1–4 Hz) are the most prominent EEG feature of human non-rapid eye movement (NREM) sleep, which have their origin in the cortical layer. Several studies proposed them as sensors for weighing synaptic efficacy and possible effectors of sleep-dependent synaptic plasticity [ 37 , 38 ]. Furthermore, wakefulness delta power increase was correlated with TMS-induced LTP-like plasticity in healthy subjects [ 37 ] and in patients with chronic stroke [ 39 ], as well as with local sleep regulation, functionally linked to learning-related cortical plasticity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delta waves (1–4 Hz) are the most prominent EEG feature of human non-rapid eye movement (NREM) sleep, which have their origin in the cortical layer. Several studies proposed them as sensors for weighing synaptic efficacy and possible effectors of sleep-dependent synaptic plasticity [ 37 , 38 ]. Furthermore, wakefulness delta power increase was correlated with TMS-induced LTP-like plasticity in healthy subjects [ 37 ] and in patients with chronic stroke [ 39 ], as well as with local sleep regulation, functionally linked to learning-related cortical plasticity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects on sensory responses promise a means to alter, over extended time periods, aspects of brain function that govern perception and behavior. Follow-up studies, in particular with use of subdural large-scale recordings in chronic preparations, could further promote the development of tACS as a tool to re-adjust brain states in pathological conditions of disturbed functional connectivity [10,12,25].…”
Section: Resultsmentioning
confidence: 99%
“…Impairment of proper coupling may lead to disorders, such as AD, PD, epilepsy, schizophrenia and autism [9]. This has fueled research into noninvasive approaches to modulate and, possibly, re-adjust neural synchrony by transcranial alternating current stimulation (tACS) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in theta activity is usually caused by an alteration of the underlying brain tissue or its network [33], and specific theta/beta (4-25 Hz) oscillations of the granule cell layer in the cerebellum have been linked to cerebral cortex activity [32,34]. Di Lazzaro and colleagues have shown that cerebellar functional lesions produced by transcranial magnetic stimulation (TMS) produce an increase in theta EEG activity in frontal areas, suggesting a direct link between cerebellar dysfunction and increased EEG theta frontal activity [35].…”
Section: Discussionmentioning
confidence: 99%